The Scramble for Land Rights: Reducing Inequity Between Communities and Companies - Veit, Peter G. (2018)
Peter G. Veit POLICY SEMINAR The Future of the Commons Co-organized by IFPRI, the International Association for the Study of the Commons (IASC), and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)